Barriers to mental health care for disadvantaged adolescents: perspectives of service providers. (3rd July 2017) - Platell, Monique; Cook, Angus; Martin, Karen
ABSTRACT: Objective : To identify barriers and enablers to professional mental health service utilisation for disadvantaged adolescents from the perspective of mental health service providers. Method : This study incorporated qualitative research methods with eight semi-structured, face-to-face interviews completed with purposively recruited government, non-government and school mental health service providers. The data were collected from May to September 2015 in Perth, Western Australia. Data analysis was undertaken using content analysis. Results : Service providers identified multiple barriers and facilitators for disadvantaged adolescents accessing and using mental health services including: (1) pathways to mental health services; (2) how services listen to and interact with adolescents; (3) service environment, including youth-friendly locations and atmosphere; and (4) government and organisational policies. Discussion : These results highlight the need to simplify pathways and provide support for adolescents in negotiating the mental health system. Schools can be utilised as an important gatekeeper to mental health services. Legislation associated with adolescent mental health appears to be a barrier for adolescents in seeking or continuing with care. Service should place more emphasis on building trusted relationships with clients and developing capacity to perform outreach. Strategies to enable services to work collaboratively may reduce the risk that adolescents experience multiple referrals within the system. To reduce the impact on individuals and long-term costs, the State Government needs to make early intervention a priority and modifying the current service delivery system to be more inclusive of adolescents' perspectives. Abstract :